A joint model of heavy truck, tyres, and operating environment for tyres selection - Kolár, Petr (My University, 2015)
Improving fuel efficiency is one of the core targets when minimizing the transport cost of a vehicle combination. Hence, it is crucial to optimize the design and selection of all vehicle components, including tyres. Volvo Group Trucks Technology (GTT) and Chalmers University of Technology run a common research project TyreOpt—Fuel consumption reduction by tyre drag optimization. This master thesis is supporting the TyreOpt research project by verification of a computationally efficient model for an evaluation of the operating costs by a newly developed joint model of the vehicle, environment, and tyres, which is based on one of the existing tools within Volvo GTT. Selection of the proper Volvo GTT analysis tool, which serves as a base for the newly developed joint model, was supported by Volvo experts’ experience. Theory of tyre was reviewed in order to support modelling of the transientlinear tyre model and implementation of the rolling resistance model, which was developed within the TyreOpt research project. Representation of the computationally efficient model of the operational cycle and all relevant parameters was transformed to the newly developed model. Simple driver and power-train models were developed in order to evaluate vehicle performance for selected operational environments. Feasability of constraining events implementation to the high-fidelity model is discussed and candidates for new constraints are proposed. Verification of the computationally efficient model concludes performance and limitations of this computationally efficient model, developed within the TyreOpt research project. The tyre model is parameterised in tyre design parameters, such as tyre width, radius and pressure. The computationally efficient and the newly developed model are investigated in qualitative manner in order to list differences in behaviour under various specification parameters of the vehicle, the tyres and the operating environment. Improvements of the computationally efficient model are proposed. Sensitivity analysis aims to investigate energetic behaviour of both models with respect to changing tyre design variables. Results proved considerable influence of different fidelity of the model on transport costs, mainly due to inverse kinematic principle of computationally efficient model, which can not cope with velocity transients and different control strategies. Trends of the energy consumption for different tyre design variables are compared with the rolling resistance theory, which was summarized in the literature review.
Keywords: Transport; Farkostteknik; Transport; Vehicle Engineering